Sharia-driven sustainable business models in the energy sector: A bibliometric and systematic review - Windiani, Windiani; Nadifah, Dhofirotun; Hakim, Muhammad Saiful; Alfarizi , Muhammad (Faculty of Business & Economics, Universitas Islam Indonesia, 2026)
Purpose – This study maps global research on the integration of Sharia principles, sustainability, and energy business models using bibliometric and systematic review approaches. It identifies publication trends, thematic structures, and scholarly contributions, showing how maqasid al-Sharia values, particularly justice, well-being, and ecological responsibility, can guide ethical and sustainable energy transitions.Methodology – This study combines bibliometric analysis using Biblioshiny and VOSviewer with a PRISMA-based systematic review. The dataset covered 112 Scopus-indexed publications published between 2013 and 2025, with an annual growth rate of 32.77%. The analysis examined publication trends, citation patterns, author collaboration, thematic mapping, and keyword co-occurrence.Findings – Bibliometric evidence shows that research on Sharia-driven sustainable energy business models accelerated after 2018 and peaked in 2024. Keyword co-occurrence analysis identified seven clusters: ESG governance and CSR, green innovation, climate change and green finance, renewable energy and emission reduction, financial inclusion, ethical technology, and Islamic fintech, digital finance, and energy governance. Thematic mapping positions sustainable development, environmental management, and the circular economy as basic themes, while financial technology and banking signal emerging directions. Implications – This study supports Islamic ESG performance reporting, ethical technology, green innovation, and inclusive finance. For policymakers, it recommends regulating green sukuk, institutionalizing energy waqf, and designing incentives for renewable energy, emission reduction, and maqasid-based sustainable SDG transition pathways.Originality – This study offers an integrative bibliometric and systematic synthesis of sustainable energy business models based on Islamic ethical values.